An empirical methodology for introducing software processes. - Shull, Forrest (Software engineering notes.)
There is a growing interest in empirical study in software engineering, both for validating mature technologies and for guiding improvements of less-mature technologies. This paper introduces an empirical methodology, based on experiences garnered over more than two decades of work by the Empirical Software Engineering Group at the University of Maryland and related organizations, for taking a newly proposed improvement to development processes from the conceptual phase through transfer to industry. The methodology presents a series of questions that should be addressed, as well as the types of studies that best address those questions. The methodology is illustrated by a specific research program on inspection processes for Object-Oriented designs. Specific examples of the studies that were performed and how the methodology impacted the development of the inspection process are also described.